Drying Prunus cerasoides trees in mid-Himalayan region: calling for immediate actions - Gautam, Kamini; H S, Mahesha; Thakur, Sapna; Gautam, Ankush; Gautam, Kamlesh Chand; Kumar, Naresh (Indian Journal of Agroforestry, 2023)
Prunus cerasoides is an ecologically and economically important multipurpose tree species of Indian Himalayas, mainly utilized for its timber, fuel wood, fodder, medicinal and horticultural value. But, in the recent past there has been declining trend in the natural population of P. cerasoides owing to its poor natural regeneration as a result of poor seed set and germination. In other hands, from last few years some of the plants showed partial drying symptoms, followed by defoliation of entire plants leads to death of whole plant. To assess the extent and cause of drying of the species in mid Himalaya, a survey was conducted in nine villages belonging to the tehsil Arki, district Solan, Himachal Pradesh, India during the month of May–October 2021 covering about 30 km2 areas. Almost 60 to 95% (average: 74.66 %) of trees in the survey locations were dried out completely. Thorough observations of dried trees revealed presence of bored holes on stems and branches with maximum number on mid portion (23.80±3.76) of the tree bole, followed by primary (12.40±1.69) as well as secondary branches (10.20±0.66) and minimum on the base of the tree trunk (8.90). The exact causal agent of the infestation was not yet identified but, split opening of branches and stem showed presence longitudinal black coloured tunnels. Our initial observations point out towards infestation of insect pest belonging to the family Cerambycidae, order Coleoptera, however exact species of insect could not be traced out. Therefore, research organizations working in Himalaya can take a note of it and initiate collaborative efforts to study the status of drying of P. cerasoides in its entire natural distribution zone and identifying the exact cause of death. Besides this, a comprehensive management practice needs to be initiated to save this prestigious species from mass extinction.